Interactive contribution of hyperinsulinemia, hyperglycemia, and mammalian target of rapamycin signaling to valvular interstitial cell differentiation and matrix remodeling - Selig, Jessica I.; Krug, H. Viviana; Küppers, Caroline; Ouwens, D. Margriet; Kraft, Felix A.; Adler, Elena; Bauer, Sebastian J.; Lichtenberg, Artur; Akhyari, Payam; Barth, Mareike (Frontiers in Cardiovascular Medicine, 2022)
Diabetes and its major key determinants insulin resistance and hyperglycemia are known risk factors for calcific aortic valve disease (CAVD). The processes leading to molecular and structural alterations of the aortic valve are yet not fully understood. In previous studies, we could show that valvular interstitial cells (VIC) display canonical elements of classical insulin signaling and develop insulin resistance upon hyperinsulinemia and hyperglycemia accompanied by impaired glucose metabolism. Analyses of cultured VIC and aortic valve tissue revealed extracellular matrix remodeling and degenerative processes. Since PI3K signaling through mammalian target of rapamycin (mTOR) is involved in fibrotic processes of the heart, we aim at further functional investigation of this particular Akt-downstream signaling pathway in the context of diabetes-induced CAVD. Primary cultures of VIC were treated with hyperinsulinemia and hyperglycemia. Phosphorylation of mTOR(Ser2448) was determined by Western blot analysis after acute insulin stimulus. Inhibition of mTOR phosphorylation was performed by rapamycin. Phosphorylation of mTOR complex 1 (MTORC1) downstream substrates 4E-BP1(Thr37/46) and P70S6K(Thr389), and MTORC2 downstream substrate Akt(Ser473) as well as the PDK1-dependent phosphorylation of Akt(Thr308) was investigated. Markers for extracellular matrix remodeling, cell differentiation and degenerative changes were analyzed by Western blot analysis, semi-quantitative real-time PCR and colorimetric assays. Hyperinsulinemia and hyperglycemia lead to alterations of VIC activation, differentiation and matrix remodeling as well as to an abrogation of mTOR phosphorylation. Inhibition of mTOR signaling by rapamycin leads to a general downregulation of matrix molecules, but to an upregulation of α-smooth muscle actin expression and alkaline phosphatase activity. Comparison of expression patterns upon diabetic conditions and rapamycin treatment reveal a possible regulation of particular matrix components and key degeneration markers by MTORC1 downstream signaling. The present findings broaden the understanding of mitogenic signaling pathways in VIC triggered by hyperinsulinemia and hyperglycemia, supporting the quest for developing strategies of prevention and tailored treatment of CAVD in diabetic patients.